Financial Feasibility Analysis and Circular Economy Capitalization Strategy: A Case Study of Salmon Skin Waste Processing MSMEs (Salmontok) in Bali - Timothy Marthin; Bernard T. Widjaja (CV. Publikasi Indonesia, 2026)
The food MSME sector in Indonesia faces major challenges in terms of operational efficiency and investment visibility. This research aims to formulate a comprehensive business development plan within a period of five years, with a focus on operational transformation and strengthening the financial structure. This study used a descriptive qualitative approach with the type of applied research. Primary data was obtained through interviews, direct observations, and consumer surveys, while secondary data was obtained from the scientific literature. The financial feasibility analysis was carried out using the Net Present Value (NPV), Internal Rate of Return (IRR), Payback Period, and Break-Even Point (BEP) indicators. The results of the study show that the transformation towards